2001
DOI: 10.1073/pnas.121172298
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic proofreading models for cell signaling predict ways to escape kinetic proofreading

Abstract: In the context of cell signaling, kinetic proofreading was introduced to explain how cells can discriminate among ligands based on a kinetic parameter, the ligand-receptor dissociation rate constant. In the kinetic proofreading model of cell signaling, responses occur only when a bound receptor undergoes a complete series of modifications. If the ligand dissociates prematurely, the receptor returns to its basal state and signaling is frustrated. We extend the model to deal with systems where aggregation of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 29 publications
2
55
0
Order By: Relevance
“…Possibly, the anomalous results reflect an inactivation of phosphorylated Syk (25). However, the model described in the accompanying paper does not predict the results if such a step is introduced (26). Likewise, the data are not explained by postulating that some of the phosphorylated Syk dissociates from the aggregated receptors but remains phosphorylated for a time consistent with results from experiments in which receptors were disaggregated with hapten (26).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Possibly, the anomalous results reflect an inactivation of phosphorylated Syk (25). However, the model described in the accompanying paper does not predict the results if such a step is introduced (26). Likewise, the data are not explained by postulating that some of the phosphorylated Syk dissociates from the aggregated receptors but remains phosphorylated for a time consistent with results from experiments in which receptors were disaggregated with hapten (26).…”
Section: Discussionsupporting
confidence: 72%
“…However, the model described in the accompanying paper does not predict the results if such a step is introduced (26). Likewise, the data are not explained by postulating that some of the phosphorylated Syk dissociates from the aggregated receptors but remains phosphorylated for a time consistent with results from experiments in which receptors were disaggregated with hapten (26). Similarly, neither the basic nor modified models predict the delay in the maximum phosphorylation of Syk achieved by the low-affinity ligand (Fig.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…These results suggested that not all responses to signaling cascades, which otherwise seemed to involve kinetic proofreading, followed the expected traits of such a system. In the theoretical treatment of this model system explored by Hlavacek et al (2), the authors provide insights into how it is possible to have discordant results like this in a system that nevertheless has properties consistent with kinetic proofreading. The authors offer several possible routes for responses to escape the intrinsic kinetic proofreading of the initial signaling events.…”
mentioning
confidence: 99%
“…One general formulation of the reaction cascade has been termed kinetic proofreading. Two papers in this issue of PNAS, Liu et al (1) and Hlavacek et al (2), examine the characteristics of a reaction in rat basophilic leukemia cells, which have been shown previously to have behavior consistent with a kinetic proofreading scheme. The experimental study by Lui et al presents evidence for a response in these cells that does not follow the kinetic proofreading scheme, whereas the second paper explores the theoretical underpinnings that allow a response to escape from kinetic proofreading.…”
mentioning
confidence: 99%